A Framework for a New Paradigm of Opioid Drug Tapering Using Adjunct Drugs - Veronin MA; Reinert JP (Substance Abuse and Rehabilitation)
Michael A Veronin,1 Justin P Reinert2 1Department of Pharmaceutical Sciences and Health Outcomes The University of Texas at Tyler Ben and Maytee Fisch College of Pharmacy, Tyler, TX, USA; 2Department of Pharmacy Practice The University of Toledo College of Pharmacy and Pharmaceutical Sciences, Toledo, OH, USACorrespondence: Michael A Veronin, Email mveronin@uttyler.eduAbstract: The misuse of and dependency on prescription opioids represents a significant crisis at the national level, impacting not only the health of the public but also the societal and economic well-being. There is a critical need for strategies to reduce the dosage of prescribed opioids to limit opioid-associated adverse effects and lower the risk of addiction development in patients experiencing chronic pain. Opioid-sparing medications, when co-administered with opioids, enable a reduced opioid dose without loss of efficacy. This suggests the potential for using opioid adjunct drugs in opioid tapering, whereby opioid doses are lowered incrementally in a systematic manner to improve a patient’s safety profile or quality of life. The objective of this report is two-fold: 1) to illustrate the potential for adjunct drugs in opioid tapering, and 2) to describe the steps needed to be taken to develop a framework for the use of adjunct drugs in opioid tapering. This can provide the impetus for further investigation into opioid tapering and the development of improved clinical care. The proposed project implements knowledge synthesis methods to develop the framework for a new paradigm of opioid drug tapering that incorporates opioid dosage reductions with adjunct drugs. Framework development is organized into three major phases: 1) Adjunct drug characterization, 2) Assessment of the opioid-sparing effect, and 3) Usability of data for clinicians. The knowledge gained from this project can provide a foundation for improved analgesia protocols for opioids and adjunctive drug therapy.Keywords: opioid adjunct, opioid-sparing, opioid tapering, addiction risk, knowledge synthesis